SOIL ATTACK: A Problem-based Learning Adventure - Chee-Ming Chan; Muhammad Daniel Hafiz Abu Amin (2024)
Problem-based learning (PBL) is routinely incorporated in students’ learning, especially in the core subjects of Civil Engineering Technology. This book tells the stories of students enrolled in the Soil Mechanics & Foundations (BNP20903) class from March till July 2023: On self-reflections, review and experience of the learning process. Assigned a road embankment failure project, the students embarked on an exciting 14-week journey of problem-solving in a structured and guided manner, though with much freedom in the direction and organization of their respective team endeavours. Many have expanded their learning horizons with industrial engagement and interaction, research investigation of archives and past records as well as delving into exploration of other disciplines and areas of study for creative ideas and solutions. THIS is their journey, experience and story.